Aesthetics and Dramaturgies of Immersive and Interactive Theatre Since the Turn of the Millennium: SIGNA – Poste Restante – Sisters Hope - Skjoldager-Nielsen, Kim (Nordic Theatre Studies, 2022)
Since the turn of the millennium, stage art has seen an increased interest in adopting and developing interactive and immersive aesthetics. This article offers a comparative study of two Danish groups, SIGNA and Sisters Hope, and one Swedish group, Poste Restante. The visual dimension of the performances by these three groups is striking, which may be partly attributed to the interconnections between the artists that has allowed a flow of ideas and strategies to occur between one group and the other. Looking at these connections, it appears that there is a line going from SIGNA (established in 2001) to Poste Restante (established in 2007) and to Sisters Hope (established in 2014). Whilst there are similarities, there are also great differences in terms of the aesthetics and dramaturgies of these groups, which reflect political, ethical, and ideological differences in the context of Nordic societies. The paper investigates these aspects through their relations to the audience: how is the audience included in a performance? And what is the purpose of applying an interactive and immersive aesthetics?